2016
DOI: 10.1111/pan.12869
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the airway after mandibular distraction osteogenesis surgery in children with temporomandibular joint ankylosis and mandibular hypoplasia

Abstract: Mandibular distraction osteogenesis improved laryngeal view. Distraction osteogenesis can be successfully used for the treatment of obstructive sleep apnea in mandibular hypoplasia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…Our results show that 43% children (26/60) improved laryngeal exposure and decrease intubation difficulty under direct laryngoscopy during the secondstage operation. These results are consistent with those of previous studies that mandibular distraction osteogenesis could improve the laryngeal view, increase the airway volume and mandibular volume [14][15][16]. However, some complications can occur after surgical correction, such as infection and ankylosis of the temporomandibular joint, which can cause intubation to be more difficult.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that 43% children (26/60) improved laryngeal exposure and decrease intubation difficulty under direct laryngoscopy during the secondstage operation. These results are consistent with those of previous studies that mandibular distraction osteogenesis could improve the laryngeal view, increase the airway volume and mandibular volume [14][15][16]. However, some complications can occur after surgical correction, such as infection and ankylosis of the temporomandibular joint, which can cause intubation to be more difficult.…”
Section: Discussionsupporting
confidence: 92%
“…In another study, Zanaty O and colleagues have concluded that DO of mandible results in marked improved in apnea-hypopnea index in patients of obstructive sleep apnea. 6 It has been shown that DO can also result in avoidance of need of tracheostomy in infants and young patients with severe airway obstruction due to mandibular micrognathia. 7 TMJ ankylosis and associated dentofacial deformities can be surgically managed by single-stage or multistage treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the narrow area of the upper airway was the retroglossal section rather than the retropalatal area, owing to the small mandible and the normal maxilla (SNA angle within the normal range). Therefore, the third treatment option was rejected because a small retroglossal area can be entirely corrected by mandibular DO with sliding genioplasty, as previously reported [ 4 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular distraction osteogenesis (DO), which has now been proposed as an alternative to bilateral sagittal split osteotomy (BSSO), is an effective method for expanding the pharyngeal airways of pediatric [ 4 ] and adult patients [ 5 , 6 ]. It has been shown that mandibular DO results in significant changes in pharyngeal airway volume [ 6 ] and the apnea-hypopnea index (AHI) [ 5 , 7 ] because more than half of upper pharyngeal airway obstructions occur at the base of the tongue [ 8 ]. Mandibular DO, which induces gradual movement of skeletal bone and slow stretching of the soft tissue, is considered to reduce the risk of relapse.…”
Section: Introductionmentioning
confidence: 99%